Global youth as catalysts for legal and sustainable wildlife trade solutions - Anagnostou, Michelle; Ng, Celine Boon Yuan; Cepeda, Robin; Lee, Jessica Grace Huiyi; Loo, Adrian Hock Beng; Ng, Peng Xiong Keith; Sitjar, Keanu; Tan, Hui Min Steffi; Tang, Yong Jen; Ting, Wai Kit (Frontiers in Conservation Science, 2025)
Despite gaining traction in international forums, such as in global climate action spheres, the potential of youth in contributing to a legal and sustainable international wildlife trade remains under-tapped, overlooked and underexplored. This is an emerging topic of discussion, as Parties to the Convention on International Trade in Endangered Species (CITES) were first encouraged to explore opportunities to engage youth during the seventeenth meeting of the Conference of the Parties in 2016. In April 2024, the first meeting of the CITES Global Youth Network was held in Singapore, where concrete actions were collaboratively identified by youth from around the world. This paper aims to answer the following question: how may youth contribute to achieving the goals of the CITES Strategic Vision by 2030? As a first step in answering this question, this community case study collates the diverse voices of members of the CITES Global Youth Network. Using a backcasting perspective, and the CITES Strategic Vision as our desired future by 2030, we outline how youth may contribute to achieving the Vision, and offer ideas of how youth can be supported. We argue that youth are underrepresented voices in wildlife trade decision-making, and that their deeper and more meaningful engagement in CITES processes has significant potential to improve outcomes for a legal and sustainable wildlife trade in the long-term and fundamental to achieving intergenerational equity as envisioned by the Sustainable Development Goals.